Lift-off detection system using Error Compensated Eddy Current Testing based on fuzzy logic - Kharudin, Ali (2017)
Nondestructive testing (NDT) deals with the inspection of an object for determining its properties without destroying its usefulness. Applications include detection of cracking in coating industries, steam generator tubing in nuclear power plants, aircraft and etc. As a method for NDT, the eddy current testing is also used for detection the lift-off in the pipe or plate due to several factors resulting from lift-off including the thickness of the coating on the pipe, the probe is lifted and the angle of pipe joining is small. In this thesis, the development of Error Compensation of Eddy Current Testing system (ECECT) and combining of the Absolute probe (AP) and Differential probe (DP) is used in measurement for actual defect measuring. From here the probe design (2D and 3D) and development are used for integrating with the system design and at the same time, the comparison between conventional technique and ECECT technique can be executable. Besides, the comparison between simulation and actual devices is used for accuracy of measurement in this system. The ECECT system design has higher sensitivity and less noise comparing conventional technique. As the complementary in this system, the Mamdani Fuzzy Logic is used as an intelligent technique in ECECT for high accuracy results. In system development, the graphical interfacing (GUI) is used for graph display on the computer by using MATLAB software and from here the value of defect and lift-off can be identify based on graph display. Based on the results was obtained ECECT system will achieve 99.90% accuracy without lift-off and 99.00% with the different types of lift-off. This shows that the merger of the probe and intelligence system are built will affect the accuracy of the results and it's very useful for the defects classification aside from the accuracy of the reading displayed. In addition, the comparison between the simulation and actual devices by using ECECT is also conducted to obtain the desired result accuracy.